SF-36 questionnaire population quality of life indices Objective - V N Amirdjanova; D V Goryachev; N I Korshunov; A P Rebrov; V N Sorotskaya (Научно-практическая ревматология)
To standardize general quality of life (QL) questionnaire SF-36 scales and calculate population scale measures depending on respondents sex and age. Material and methods. Standardized QL measures of all SF-36 questionnaire scales were calculated in 3400 respondents of 5 centers of Russian Federation stratified according to sex and age. Results. Male population had better QL measures than female (p<0,0001) in all SF-36 questionnaire scales. QL measures of physical, role and physical functioning scales in respondents younger than 45 years of age were above mean values. In this age group pain did not have a significant influence on QL. Health general state was above mean level in respondents younger than 35 years. Regardless of sex they had higher social activity and vital capacity scale measures. Male mental health was higher than mean values till 75 years of age. In women these measures decreased beginning from 35 years of age. Conclusion. Reference base of SF-36 questionnaire standardized measures population values can be used for comparison of QL of pts with different diseases according to age and sex as well as for treatment efficacy assessment in scientific studies.